Use of single dose prophylactic magnesium sulphate in severe preeclampsia in preventing seizures - Bembalgi, Shobha; Kanwal, Preet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preeclampsia is a pregnancy specific multi organ disease process characterized by de novo development of hypertension and proteinuria after 20 weeks of gestation. Preeclampsia complicates 2-8% of pregnancies. Methods: We have studied 100 patients with severe preeclampsia who were randomly divided into two groups. One group received 4 gm intravenous MgSO4 on admission which was prepared by diluting in 10 ml normal saline and was given over 10-12 minutes slowly with strict monitoring. 50 patients of severe pre-eclampsia with B.P>160/110 mm of Hg were given the prophylactic dose and rest 50 acted as controls. Monitoring of B.P., urine output; respiratory rate and FHS was done. Results: We have 1 case of seizure after 8 hours of giving loading dose, which was changed to Pritchard’s regimen for further management whereas 7 patients had in the control groups. There were no cases of magnesium toxicity seen. There were no cases of maternal deaths and postpartum convulsions. Conclusions: Single loading dose of magnesium sulphate is an efficient prophylactic in preventing eclampsia.